Development of novel organocatalysts towards the kinetic and dynamic resolution of chiral enolisable anhydrides - CLAVEAU, ROMAIN (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2018)
In this thesis we explore the possibilities offered by the bifunctional properties of a series of organocatalysts derived from cinchona alkaloids for the promotion of novel asymmetric transformations. In particular, we focused our attention on the extention of the scope of enantioselective cycloaddition reactions of pronucleophilic anhydrides capable of reacting with electrophiles such as aldehydes and of yielding chiral lactones in a regio-, diastero- and enantioselective fashion. We have shown for the first time that a series of trans-disubstituted aryl succinic anhydrides can participate in a unique one-pot formal cycloaddition process with aldehydes via dynamic kinetic resolution (DKR). The highly functionalised butyrolactones products are important members of a class of compounds possessing a wide array of valuable biological properties (paraconic acid derivatives). An ad hoc designed squaramide organocatalyst was able to promote the reaction, at 5 mol% loading, furnishing the lactones with good to excellent stereocontrol over three chiral centres, one of which being all-carbon quaternary in nature (up to 92%, 34:1 dr, 98% ee). The synthetic utility of these compounds as potential building blocks for organic syntheses was demonstrated through ready manipulation of one of the products to form a stereochemically dense and complex fused lactone-lactam system in 86% ee. We later extended the methodology to the more challenging kinetic resolution (KR) variant of the process and reacted a-alkylated aryl sucinnic anhydrides in a regio-, diastereo- and enantioselective cycloaddition with aldehydes. The first examples of the KR of these starting materials provided access to a range of chiral succinate derivatives with selectivity factors up to S* = 10.5. Densely functionalised five-membered lactones (paraconic acid derivatives, y-butyrolactones) could be formed, in one pot, with control over three contiguous stereocentres and selectivities ranging from modest to excellent (up to 7:1 dr, 94% ee). This project also reports the first examples of a promising ad hoc designed novel class of bifunctional hydrogen-bond donor sulfamide organocatalyst capable of engaging in multiple hydrogen-bonds with the substrates.
APPROVED
Keywords: (dynamic) kinetic resolution, cycloaddition reaction, enolisable anhydrides, diastereoselectivity, enantioselectivity